Dominant-negative signal transducer and activator of transcription (STAT)3 variants in adult patients: A single center experience - Shamriz, Oded; Rubin, Limor; Simon, Amos J.; Lev, Atar; Barel, Ortal; Somech, Raz; Korem, Maya; Matza Porges, Sigal; Freund, Tal; Hagin, David; Garty, Ben Zion; Nahum, Amit; et al. (Frontiers in Immunology, 2022)
Background: Autosomal dominant hyper-IgE syndrome (AD-HIES) caused by dominant negative (DN) variants in the signal transducer and activator of transcription 3 gene (STAT3) is characterized by recurrent staphylococcal abscesses, severe eczema, chronic mucocutaneous candidiasis (CMC), and non-immunological facial and skeletal features. Objectives: To describe our experience with the diagnosis and treatment of adult patients with AD-HIES induced by DN-STAT3 variants. Methods: The medical records of adult patients (>18 years) treated at the Allergy and Clinical Immunology Clinic of Hadassah Medical Center, Jerusalem, Israel, were retrospectively analyzed. Immune and genetic workups were used to confirm diagnosis. Results: Three adult patients (2 males; age 29-41 years) were diagnosed with DN-STAT3 variants. All patients had non-immunological features, including coarse facial habitus and osteopenia. Serious bacterial infections were noted in all patients, including recurrent abscesses, recurrent pneumonia, and bronchiectasis. CMC and diffuse dermatophytosis were noted in two patients. Two patients had severe atopic dermatitis refractory to topical steroids and phototherapy. Immune workup revealed elevated IgE in three patients and eosinophilia in two patients. Whole exome sequencing revealed DN-STAT3 variants (c.1166C>T; p.Thr389Ile in two patients and c.1268G>A; p. Arg423Gln in one patient). Variants were located in DNA-binding domain (DBD) and did not hamper STAT3 phosphorylation Treatment included antimicrobial prophylaxis with trimethoprim/sulfamethoxazole (n=2) and amoxycillin-clavulanic acid (n=1), and anti-fungal treatment with fluconazole (n=2) and voriconazole (n=1). Two patients, who had severe atopic dermatitis, were treated with dupilumab with complete resolution of their rash. No adverse responses were noted in the dupilumab-treated patients. Discussion: Dupilumab can be used safely as a biotherapy for atopic dermatitis in these patients as it can effectively alleviate eczema-related symptoms. Immunologists and dermatologists treating AD-HIES adult patients should be aware of demodicosis as a possible manifestation. DN-STAT3 variants in DBD do not hamper STAT3 phosphorylation